The term «phraseme» in etnolinguistics and linguistic culture (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
In the article historical-etymology base of the term «phraseme» and its internal structure are analyzed. The structural features of phraseological units are researched. The methodological and theoretical principles of phraseological composition of the language are considered. The relationship of cultural and ethnographic factors are trased.
Keywords: phraseme; phraseology; phraseological units; ethnolinguistics; linguistic culture; linguistic picture of the world